PSYCHOLOGICAL FEATURES OF READAPTATION OF POST-COMBATANTS AFTER THE RETURN FROM THE COMBAT ZONE - Voshkolup Hanna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article is devoted to the problem of psychological features of readaptation of post-combatants after returning from the combat zone. The aims of the article are the substantiation and experimental study of the psychological features of readaptation of post-combatants to peaceful life. The tasks are defined as elucidating the essence of the concept of “readaptation” in scientific research, determination of psychological features of readaptation of post-combatants to peaceful life, and conducting a study of psychological features of readaptation of post-combatants to peaceful life. The following methods were used, including theoretical (analysis, generalization, comparison, and systematization), and empirical ones (multi-level personality questionnaire “Adaptivnist-200”). It has been established that the “readaptation” concept is applied when it comes to the need of an individual to “fight” against the psych-traumatic consequences of various stressful situations, as a result of which personality’s re-adaptation to ordinary life should take place after experiencing extreme situations. A critical analysis of approaches to defining the essence of the concept of “readaptation” by various researchers has been carried out. It has been emphasized that the process of readaptation of an individual can take place in two ways. In the first case, the person aligns their actions with the real situation on the basis of their own social experience, and in the second case, they transform the social situation to allow for their own life needs as a result of assimilating new norms, stereotypes and principles of social behaviour. It has been found out that the maladaptation of post-combatants can be pathological and non-pathological in nature. The non-pathological maladaptation is formed through individual deviations in the subject’s behaviour and experiences, caused by insufficient resocialization, socially unacceptable individual attitudes after returning from the combat zone, the breakdown of significant interpersonal relationships, the inability to engage in usual work or continue education due to injuries or mutilation etc. It has been shown that the system of rehabilitation of post-combatants has to be based on a complex of methods, principles, norms, laws and procedures which should take into account both non-pathological and possible pathological signs of post-traumatic stress disorders, as well as their depth and significance for the post-combatant’s life. The key goal of readaptation at the stage of the post-combatants’ exit from the combat zone is to satisfy their natural needs (recognition, understanding, and protection). Considering today’s requirements and the growing number of post-combatants who need psychological help, a corresponding study of their adaptability indicators was conducted via the BOO “Adaptivnist-200” methodology. Within the framework of this methodology, the levels of the personal potential of socio-psychological adaptation of post-combatants were calculated, which proved the prevalence of low resistance to combat stress. In addition, the following results were fixed including: mostly the sufficient level of military-professional orientation, the presence of some signs of deviant behaviour as well as the existence of individual rates of suicidal tendency. According to the results of the conducted research, practical psychological recommendations are proposed including more comprehensive approaches to improving the level of post-combatants’ readaptation to a peaceful life.